2016
DOI: 10.7314/apjcp.2016.17.3.1449
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome and Predictors of Survival in Thai Adult Rhabdomyosarcoma Cases

Abstract: Background: Adult rhabdomyosarcoma (RMS) is a rare and aggressive disease with limited data compared with pediatric RMS. The goal of this study was to determine the treatment outcome and identify factors related to survival outcome in Thailand. Materials and Methods: Adult patients (≥15 years old) with the pathological diagnosis of RMS between 1985 and 2010 were reviewed. The data were retrospectively reviewed from the pathological results and medical records from Srinagarind Hospital, Khon Kaen University. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some studies included children as young as three years of age. Four studies reported their population consisted of “adult patients” but included patients as young as 15 years of age . In one study that did stratify by age, their pediatric ( < 18 years) and adult ( > 15 years) populations overlapped .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies included children as young as three years of age. Four studies reported their population consisted of “adult patients” but included patients as young as 15 years of age . In one study that did stratify by age, their pediatric ( < 18 years) and adult ( > 15 years) populations overlapped .…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported their population consisted of "adult patients" but included patients as young as 15 years of age. [32][33][34][35] In one study that did stratify by age, their pediatric ( < 18 years) and adult ( > 15 years) populations overlapped. 35 Ultimately, the inclusion of patients aged 15 to 17 years in several well-designed, relevant cohort studies lamentably precluded them from being included in our analysis.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The use of radiotherapy was also associated with better survival of the patients both in the local disease stage, as well as for disseminated disease [147,200,201]. Including chemotherapy was found to be an independent prognostic factor causing lower mortality due to the progress of the neoplastic disease according to the analysis of patients from a center in Thailand [202]. There are, however, also reports on the lack of improvement of survival of patients subjected to chemotherapy in comparison to a control group [201].…”
Section: Rms In Adult Patients -Selected Aspectsmentioning
confidence: 98%